Late-onset neutropenia after rituximab in ANCA-associated vasculitis. (2nd September 2016) - Knight, A; Sundström, Y; Börjesson, O; Bruchfeld, A; Malmström, V; Gunnarsson, I
Abstract : Background : Rituximab (RTX) is being used increasingly in anti-neutrophil cytoplasmatic antibody (ANCA)-associated vasculitis (AAV). Late-onset neutropenia (LON) and risks of infections have been observed following RTX therapy in rheumatological diseases including granulomatosis with polyangiitis (GPA) but data on microscopic polyangiitis (MPA) are lacking. Method : We studied the occurrence of LON in 59 AAV (47 GPA/12 MPA) patients treated with RTX. Patient charts were retrospectively reviewed for the occurrence of LON and clinical data were extracted and included in the analysis. Results : Seven of the total 59 patients (11.9%) developed LON after a median time of 86 days (range 56–168 days) since their latest RTX treatment. Of these seven LON patients, 5/47 (10.6%) had a diagnosis of GPA and 2/12 (16.7%) of MPA. Three of the patients developed LON after the first RTX treatment and four had received repeated courses. Five LON patients developed infectious symptoms. Six of the patients were hospitalized. Retreatment with RTX was given in three cases without further LON episodes. Conclusions : LON is a potentially severe side-effect of RTX occurring in both GPA and MPA and may develop after both single and repeated treatment courses. As infections are commonly seen, the condition requires an increased awareness. No predisposing factors for LON were identified.